Place of Death of Cancer Patients Treated at a German Comprehensive Cancer Center - Julia Berendt; Maria Heckel; Christoph Ostgathe; Stephanie Stiel; Peter Stachura; Andreas Becker; Matthias W. Beckmann; Susanne Gahr (Palliative Medicine Reports)
Background: Public health research includes end-of-life care. Place of death is an indicator of end-of-life care quality. Objective: We assessed the place of death of cancer patients treated at a Comprehensive Cancer Center (CCC), caring for an average of 2220 primary cases per year. Methods: Dataset includes information on cancer patients who were treated at least once in a German CCC, died between 2009 and 2013, and for whom a place of death could be assigned. Data—reported following the “REporting of Studies Conducted Using Observational Routinely Collected Data” guideline—were retrieved from death registration and analyzed retrospectively. Descriptive analyses, frequency calculations, Pearson/Cramer’s V chi-square tests, and t tests in SPSS 28.0 were used. Results: A total of 5855 patients were analyzed (metastases n = 2830, 48.3%; recurrent cancer n = 1930, 33.1%). Finally, 3523 (60.2%) died in a clinical setting (CCC: 28.9%/other hospital: 31.3%). Patients who died in the CCC (mean age 66.3 years) were younger than those who died in other hospitals (mean age 67.8 years; p = 0.034) or at home (ø 70.2 years; p = 0.000). Cancer patients who died in the CCC (n = 1693) had over time a median of 356 contacts with specialized palliative care within 30 days before death (standard deviation [SD]: 319–377, mean 352). One-third of patients died within one year of diagnosis (p < 0.001). For patients dying in the CCC, the rate was even higher (50.6%, p < 0.001). Conclusion: Even if treated in certified centers, CCC cancer patients have a high in-hospital mortality rate. The place of death reflects care structures and disease progression, highlighting the need for palliative care. As frequent death sites, CCCs should offer specialized palliative services. Further research is needed to better align the place of death with patient wishes.